Building the Pesantren Reputation: Implementation of Inbound Marketing - Baharun, Hasan; Wibowo, Adi; Rizal, Himmatur (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study explores Islamic boarding schools' (pesantren) inbound marketing reputation-building, which focuses on content that is relevant, interesting and of high value to influence public perception. This study uses a descriptive qualitative approach with data collection techniques through interviews, accurate documentation, and researcher observations at the Nurul Jadid Islamic Boarding School. This study reveals four research findings: first Attract, second Convert, third Close, and fourth Delight in implementing inbound marketing at the Nurul Jadid Islamic Boarding School. From this research, the inbound marketing strategy of Nurul Jadid has a positive impact on public perception of it. By providing relevant and high-quality content, Islamic boarding schools can build better community relationships and a strong reputation in the current technological era. They are expected to be able to produce educational content, such as articles and videos, which can influence public perception. Through social media, websites and other digital platforms, Islamic boarding schools can build active and positive online communities. With consistency in conveying Islamic boarding school messages and values, public perception will become better and more inclusive. This research can provide valuable insight for traditional Islamic educational institutions in utilizing modern marketing techniques, such as inbound marketing, to develop the reputation of Islamic boarding schools in the digital era. Apart from that, the results of this research can also contribute to the literature on marketing strategies in the educational context.